2017
DOI: 10.1183/13993003.01493-2017
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal staging by videomediastinoscopy in clinical N1 non-small cell lung cancer: a prospective multicentre study

Abstract: A quarter of patients with clinical N1 (cN1) non-small cell lung cancer (NSCLC) based on positron emission tomography-computed tomography (PET-CT) imaging have occult mediastinal nodal involvement (N2 disease). In a prospective study, endosonography alone had an unsatisfactory sensitivity (38%) in detecting N2 disease. The current prospective multicentre trial investigated the sensitivity of preoperative mediastinal staging by video-assisted mediastinoscopy (VAM) or VAM-lymphadenectomy (VAMLA).Consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…Both techniques have a sensitivity close to 90% and a specificity of 100% [17,[22][23][24][25]. However, if the result is negative, not assessable or not sufficiently reliable (NPV: < 90%), staging must be completed with surgical techniques [24,26,27].…”
Section: Non-surgical Intrathoracic Invasive Stagingmentioning
confidence: 99%
“…Both techniques have a sensitivity close to 90% and a specificity of 100% [17,[22][23][24][25]. However, if the result is negative, not assessable or not sufficiently reliable (NPV: < 90%), staging must be completed with surgical techniques [24,26,27].…”
Section: Non-surgical Intrathoracic Invasive Stagingmentioning
confidence: 99%
“…Endosonography for mediastinal/hilar nodal staging in early stage non-small cell lung cancer In patients with tumours classified as clinical N0 at PET-CT, recent studies reported a risk of mediastinal nodal involvement of <20% and sensitivity of 0.17-0.41 for EBUS-TBNA to detect mediastinal nodal disease [63][64][65][66]. Two prospective multicentre studies reported a risk of mediastinal nodal involvement of 25% in 205 patients classified as clinical N1 at PET-CT [67,68]. In resectable patients classified as clinical N1 at PET-CT, a sensitivity of 0.38-0.53 has been reported for endosonography to detect mediastinal nodal disease [66,67,69].…”
Section: Endoscopic Techniquesmentioning
confidence: 99%
“…Overall, the routine use of a preoperative EBUS-TBNA for systematic mediastinal nodal sampling in clinical stage I−IIB non-small cell lung cancer has only a moderate sensitivity to detect mediastinal nodal disease and does not greatly increase the negative predictive value of PET-CT [63][64][65][66][67][68]. In the concepts of Bayesian decision analysis, given a pre-test prevalence of 10-25% and sensitivity for EBUS-TBNA of less than 50% to detect mediastinal nodal disease in early stage non-small cell lung cancer, a post-test probability of greater than 10% is expected requiring another invasive staging test, taking into account the testing decision threshold of 10% required by the ESTS guidelines [2].…”
Section: Endoscopic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This article reports the findings of a prospective clinical trial by D ecaluwé et al . [ 11 ]. Investigators attempted to evaluate preoperatively the sensitivity of video-assisted mediastinoscopy (VAM) or VAM–lymphadenectomy (VAM(LA)) in mediastinal staging of operable and resectable suspected NSCLC and clinical N1 disease (cN1).…”
mentioning
confidence: 99%